Twin studies: A unique epidemiological tool - Monalisha Sahu; Josyula G Prasuna (Wolters Kluwer Medknow Publications, 2016)
Twin studies are a special type of epidemiological studies designed to measure the contribution of genetics as opposed to the environment, to a given trait. Despite the facts that the classical twin studies are still being guided by assumptions made back in the 1920s and that the inherent limitation lies in the study design itself, the results suggested by earlier twin studies have often been confirmed by molecular genetic studies later. Use of twin registries and various innovative yet complex software packages such as the (SAS) and their extensions (e.g., SAS PROC GENMOD and SAS PROC PHREG) has increased the potential of this epidemiological tool toward contributing significantly to the field of genetics and other life sciences.